Morphogenesis-inspired two-dimensional electrowetting in droplet networks. (1st May 2023) - El-Beyrouthy, Joyce; Makhoul-Mansour, Michelle; Gulle, Jesse; Freeman, Eric
Abstract: Living tissues dynamically reshape their internal cellular structures through carefully regulated cell-to-cell interactions during morphogenesis. These cellular rearrangement events, such as cell sorting and mutual tissue spreading, have been explained using the differential adhesion hypothesis, which describes the sorting of cells through their adhesive interactions with their neighbors. In this manuscript we explore a simplified form of differential adhesion within a bioinspired lipid-stabilized emulsion approximating cellular tissues. The artificial cellular tissues are created as a collection of aqueous droplets adhered together in a network of lipid membranes. Since this abstraction of the tissue does not retain the ability to locally vary the adhesion of the interfaces through biological mechanisms, instead we employ electrowetting with offsets generated by spatial variations in lipid compositions to capture a simple form of bioelectric control over the tissue characteristics. This is accomplished by first conducting experiments on electrowetting in droplet networks, next creating a model for describing electrowetting in collections of adhered droplets, then validating the model against the experimental measurements. This work demonstrates how the distribution of voltage within a droplet network may be tuned through lipid composition then used to shape directional contraction of the adhered structure using two-dimensional electrowetting events. Predictions from this model were used to explore the governing mechanics for complex electrowetting events in networks, including directional contraction and the formation of new interfaces.